Dispensation of Marriage on the Grounds of Dating: A Case Study at the Sungai Penuh Religious Court in 2023 - Artia, Eli; Zufriani; Iskandar, Nuzul (Al-Risalah, 2025)
This study examines the judicial considerations in granting marriage dispensation at the Sungai Penuh Religious Court, particularly focusing on cases where applicants cited dating as a primary reason. The research aims to analyze the factors influencing judicial decisions beyond legal certainty, emphasizing the role of social and religious considerations. A qualitative case study approach was employed to provide an in-depth understanding of judicial decision-making. Data collection involved interviews with court clerks and an analysis of court decision documents to identify the key determinants shaping judges' rulings. The findings reveal that judges' decisions are not solely based on legal certainty but are influenced by multiple factors, including the physical and mental readiness of the prospective spouses, the duration of their relationship, and the urgency of the social context. The application of fiqh principles and maqāṣid sharī‘ah played a crucial role in ensuring that rulings prioritized the protection of children's lineage (nasab) and the prevention of adultery. This study offers a unique perspective on marriage dispensation by highlighting the intersection of legal, social, and religious considerations in judicial decision-making. It contributes to the broader discourse on Islamic family law in Indonesia and the evolving role of judges in applying fiqh-based principles to contemporary issues. The findings provide valuable insights for legal practitioners, policymakers, and scholars in understanding the dynamics of marriage dispensation cases. This research can serve as a reference for future studies on judicial discretion and the implementation of Islamic legal principles in Indonesia's religious courts.